2001
DOI: 10.1034/j.1399-0004.2001.600206.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype variability of two FAP families with an identical APC germline mutation at codon 1465: a potential modifier effect?

Abstract: We report the cases of two familial adenomatous polyposis (FAP) families who presented with the same 2 base pair deletion (AG) at codon 1465 of the adenomatous polyposis coli (APC) gene, but showed phenotypic variability. The mutation was revealed by a simple nonradioactive method using a heteroduplex analysis and identified by a sequence analysis. This observation suggests the responsibility of modifier genes in FAP patients' phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Mutations in these genes have been shown to drive Wnt signaling in other tumors (17)(18)(19); however, the effect of these specific mutations on Wnt signaling in MM remains to be established. In addition, in analyzing the data of Mulligan et al (44) involving targeted sequencing of established oncogenes, we identified a T41I mutation in β-catenin (CTNNB1) and a frameshift mutation in APC (S1465fs*3), both of which have been shown to drive oncogenic Wnt signaling (45,46). Thus, these mutations might represent alternative mechanisms driving Wnt signaling in a subset of MMs.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in these genes have been shown to drive Wnt signaling in other tumors (17)(18)(19); however, the effect of these specific mutations on Wnt signaling in MM remains to be established. In addition, in analyzing the data of Mulligan et al (44) involving targeted sequencing of established oncogenes, we identified a T41I mutation in β-catenin (CTNNB1) and a frameshift mutation in APC (S1465fs*3), both of which have been shown to drive oncogenic Wnt signaling (45,46). Thus, these mutations might represent alternative mechanisms driving Wnt signaling in a subset of MMs.…”
Section: Discussionmentioning
confidence: 99%